How Do Minimum Wages Affect Nonemployer Businesses in the United States? - Ke Lyu; Frank M. Fossen (Institute of Labor Economics (IZA), 2025)
This paper investigates the impact of minimum wage increases on nonemployer business establishments in the United States. We develop a theoretical model of occupational choice and estimate effects using panel data from the Nonemployer Statistics (2001-2020). Our identification strategy compares contiguous counties across state borders. Results show that a 1 increase in the minimum wage reduces the number of nonemployers by 0.5%-0.9%, likely due to relatively more attractive wage jobs. The effect is smaller in counties with higher shares of minorities, females, and lower education, while the transportation sector expands due to the gig economy. Further analysis reveals that higher minimum wages discourage transitions from nonemployer to employer status and increase shifts from self-employment to wage work or unemployment, showing how this regulation shapes entrepreneurship dynamics.
Keywords: J24; J38; L26; 330; minimum wages; nonemployer businesses; entrepreneurship